Parametrization for a class of rauzy fractals - Bastos, J. [UNESP]; Rodrigues de Souza, T. [UNESP] (My University, 2019)
In this paper, we study a class of Rauzy fractals Ra given by the polynomial x3 − ax2 + x − 1 where a ≥ 2 is an integer. In particular, we give explicitly an automaton that generates the boundary of Ra and using an unusual numeration system we prove that Ra is homeomorphic to a topological disk.